EFFECTIVENESS OF THE TAHFIZH AL-QUR'AN LEARNING METHOD IN FORMING THE CHARACTER OF STUDENTS AT THE MA'HAD TAHFIZHIL QUR'AN FOUNDATION OF THE ISLAMIC CENTRE OF NORTH SUMATRA - Sahla Tutia Nasution (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
This study was motivated by the increasing moral crisis and character degradation among the younger generation in the modern era, which requires strengthening character education based on religious values. This study aims to describe the effectiveness of the Qur’anic tahfizh learning method in shaping students’ character at Ma’had Tahfizhil Qur’an Yayasan Islamic Centre Sumatera Utara. A qualitative approach with a descriptive design was employed. Data were collected through observation, interviews, and documentation involving teachers, administrators, and students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings show that the Qur’anic tahfizh learning method, implemented through muroja’ah activities, halaqah, memorization deposits, worship habituation, and teachers’ role modeling, effectively contributes to the development of students’ religious character, discipline, responsibility, and noble morals. A conducive boarding school environment also supports the character-building process. However, several challenges were identified, including the low motivation of some students and the influence of digital technology, which may reduce students’ learning focus. These findings indicate that Qur’anic tahfizh learning plays an important role in supporting character development among students in the Islamic boarding school environment.